Zinc concentrations in teeth of female walruses reflect the onset of reproductive maturity. Issue 1 (13th April 2020) - Clark, Casey T; Horstmann, Lara; Misarti, Nicole
Abstract: Age at maturity is an important parameter in many demographic models and, for some species, can be difficult to obtain using traditional methods. Incremental growth structures act as biological archives, recording information throughout an organism's life and possibly allowing for the reconstruction of life history events. Concentrations of zinc (Zn) in animal tissues are known to be linked to life history, physiology and reproduction and may be retained in incremental growth structures. This study reconstructed lifetime Zn concentrations in teeth ( n = 93) of female Pacific walruses ( Odobenus rosmarus divergens ) collected from 1932–2016. Zn displayed a characteristic pattern of accumulation, with a change point marking the beginning of a lifelong, linear increase in Zn concentrations. We hypothesized that this change point marks the onset of reproductive maturity. The age at which the change point occurred (agecp ) was estimated by counting tooth cementum growth layers. These estimates closely matched literature values of timing of first ovulation in female walruses. Total number of ovulations (estimated from ovary corpora counts from paired tooth/ovary specimens) was closely related to reproductive lifespan (total lifespan – agecp ; R 2 = 0.70). Further, agecp tracked changes in Pacific walrus population size as a proportion of carrying capacity, decreasing when the population was depleted by commercial hunting and peaking when carrying capacity was exceeded. This novel approach will aid walrus management, and is likely applicable to other species, offering a potentially powerful tool for research, management and conservation of wildlife populations.